02 PEMBERDAYAAN ANGGOTA KELOMPOK TANI DALAM MENINGKATKAN KESEJAHTERAAN PETANI CABAI MERAH DI DESA LAIYA KECAMATAN CENRANA KABUPATEN MAROS - Jurnal Agribis; Aswar S.; Zulkifli Zulkifli; Andi Nur Imran (Universitas Muslim Maros, 2020)
The research method is descriptive analysis. The objectives of this study were 1) To determine the empowerment of members of the red chili farmer group in improving welfare in Laiya Village, Cenrana District, Maros Regency. 2) To determine the factors that influence the empowerment of members of the red chili farmer group in Laiya Village, Cenrana District, Maros Regency. The population in this study were 231 people and a sample of 23 people. The data used are qualitative data and quantitative data. This research was conducted in Laiya Village, Cenrana District, Maros Regency The results of this study indicate that 1) empowerment of farmer group members in Laiya Village in terms of economic and social aspects is in the high category, where in the economic aspect the empowerment value is 74.04 (high category) while from the social aspect the empowerment value is 90.49. (high category). 2) Education, farming experience, land area and ownership status greatly affect the level of empowerment of a farmer, especially farmers in Laiya Village, Cenrana District, Maros Regency. This is evidenced by the probability value of the four variables <0.005. where X1 is 0.000, so 0.000 <probability 0.005 and the value of F Count 120.313, X2 is 0.000, so that 0.000 <probability 0.005 and the value of F Count 150,859, X3 is 0.000, so 0.000 <probability 0.005 and the F value of 37.245 and X4 of 0.000 , so that 0.000 <probability 0.005 F count 44,200.